Dental Pulp Mesenchymal Stem Cells Attenuate Limb Ischemia via Promoting Capillary Proliferation and Collateral Development in a Preclinical Model. (1st September 2021) - Li, Youfeng; Zhang, Yuning; Wang, Hua; Sun, Chengfeng; Liu, Dongmei; Liu, Hongying; He, Jia; Chen, Furong; Wang, Weiting; Jiang, Xi; Wu, Chu-tse; Yang, Yuefeng
Abstract : Critical limb ischemia (CLI), an end-stage manifestation of peripheral artery disease (PAD), still lacks effective therapeutic strategies. Recently, dental pulp-derived mesenchymal stem cells (DP-MSCs) have been attracting more and more attentions in therapeutic applications due to their high proliferation ability, powerful osteogenic differentiation potential, and effective anti-inflammatory effects. In this study, we compared the therapeutic effects of MSCs derived from different sources in a femoral artery-ligated preclinical ischemic model. We found that treatments with MSCs, including bone marrow- (BM-), adipose- (AD-), dental pulp- (DP-), and umbilical cord- (UC-) derived MSCs, improved limb functions, reduced inflammatory responses, increased angiogenesis, and promoted regeneration of muscle fiber. Among them, DP-MSCs and BM-MSCs produced much more impressive effects in restoring limb functions and promoting angiogenesis. The flow velocity restored to nearly 20% of the normal level at 3 weeks after treatments with DP-MSCs and BM-MSCs, and obvious capillary proliferation and collateral development could be observed. Although neovascularization was induced in the ischemic limb after ligation, MSCs, especially DP-MSCs, significantly enhanced the angiogenesis. In vitro experiments showed that serum deprivation improved the expression of angiogenic factors, growth factors, and chemokines in DP-MSCs and UC-MSCs, but not in BM-MSCs and AD-MSCs. However, DP-MSCs produced stronger therapeutic responses than UC-MSCs, which might be due to the higher expression of hepatocyte growth factor (HGF) and hypoxia-inducible factor-1 α (HIF-1 α ). We speculated that DP-MSCs might stimulate angiogenesis and promote tissue repair via expressing and secreting angiogenic factors, growth factors, and chemokines, especially HGF and HIF-1 α . In conclusion, DP-MSCs might be a promising approach for treating CLI.